2017
DOI: 10.1186/s12933-017-0543-5
|View full text |Cite
|
Sign up to set email alerts
|

PRotective Effect on the coronary microcirculation of patients with DIabetes by Clopidogrel or Ticagrelor (PREDICT): study rationale and design. A randomized multicenter clinical trial using intracoronary multimodal physiology

Abstract: BackgroundIn diabetic patients a predisposed coronary microcirculation along with a higher risk of distal particulate embolization during primary percutaneous intervention (PCI) increases the risk of peri-procedural microcirculatory damage. However, new antiplatelet agents, in particular Ticagrelor, may protect the microcirculation through its adenosine-mediated vasodilatory effects.MethodsPREDICT is an original, prospective, randomized, multicenter controlled study designed to investigate the protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…When compared with potent inhibition of platelet function, ticagrelor and prasugrel inhibit approximately 94% and 90%, respectively, in those with aspirin, whereas clopidogrel typically achieves a maximum of only 50% platelet inhibition in combination with aspirin in ACS. Ticagrelor and prasugrel are faster than clopidogrel in reaching its peak concentration (peak effect after loading dose at 2 hours for ticagrelor, 4 hours for prasugrel, and 6 hours for clopidogrel) and has been shown to increase adenosine plasma concentration associated with an inhibition of adenosine uptake of red blood cells, stimulating vasodilatation [ 35 37 ]. In our study, microvascular injury was reduced more in the third-generation P2Y12 inhibitors group.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with potent inhibition of platelet function, ticagrelor and prasugrel inhibit approximately 94% and 90%, respectively, in those with aspirin, whereas clopidogrel typically achieves a maximum of only 50% platelet inhibition in combination with aspirin in ACS. Ticagrelor and prasugrel are faster than clopidogrel in reaching its peak concentration (peak effect after loading dose at 2 hours for ticagrelor, 4 hours for prasugrel, and 6 hours for clopidogrel) and has been shown to increase adenosine plasma concentration associated with an inhibition of adenosine uptake of red blood cells, stimulating vasodilatation [ 35 37 ]. In our study, microvascular injury was reduced more in the third-generation P2Y12 inhibitors group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, coronary microvascular dysfunction has been identified as one of the specific causes in 45% of dementia cases and 25% of strokes [8]. Through a review of several research pertaining to CMD, it was shown that clopidogrel was the most commonly prescribed medicine [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Its widespread use and prescription frequency can be linked to its anti-clotting actions and superior efficacy relative to other anti-platelet medications.…”
Section: Clopidogrel and Cmdmentioning
confidence: 99%
“…In a research study, it was observed that clopidogrel and ticagrelor are equally effective against acute coronary syndrome, although clopidogrel causes a much-reduced incidence of major and minor bleeding [29]. Clopidogrel was utilized in 14 of the studies that were evaluated in our inquiry [9][10][11][14][15][16][17][19][20][21][22][23][24][25][26][27]. In these 14 trials, clopidogrel was utilized in a range of therapeutic modalities, from antiplatelet therapy to vasodilation induction.…”
Section: Clopidogrel and Cmdmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, increased platelet reactivity may account for reduced antiplatelet effects to oral antiplatelet agents, such as clopidogrel . The mechanisms leading to the high on‐treatment platelet reactivity of clopidogrel in patients with T2DM are not fully elucidated and may potentially involve genetic factors . Thus, after the introduction of new P2Y 12 agents, the influence of ticagrelor or prasugrel on platelet reactivity was the object of studies clarifying whether these regimens have better antiplatelet effects than clopidogrel in patients with T2DM.…”
Section: What Is New and Conclusionmentioning
confidence: 99%